2017
DOI: 10.3389/fnins.2017.00299
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effects of Lipoxygenase and Cyclo-Oxygenase Inhibitors in Inflammation-Induced Human Fetal Glia Cells and the Aβ Degradation Capacity of Human Fetal Astrocytes in an Ex vivo Assay

Abstract: Chronic inflammation is a common phenomenon present in the background of multiple neurodegenerative diseases, including Alzheimer's disease (AD). The arachidonic acid pathway overproduces proinflammatory eicosanoids during these states and glial cells in the brain gradually lose their vital functions of protecting and supporting neurons. In this study, the role of different key enzymes of the eicosanoid pathway mediating inflammatory responses was examined in vitro and ex vivo using human fetal glial cells. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Chronic inflammation is a common phenomenon present in the background of multiple neurodegenerative diseases, including AD. Previous studies showed that the key regulatory enzymes in the eicosanoid pathway, i.e., cyclooxygenase-2 and 5-, 12-, and 15-lipoxygenases, appear to have an important role in mediating the pro-inflammatory responses, providing further evidence that, in the future, it may be possible to manipulate pro-inflammatory pathways for therapeutic purposes [13]. Lipoxygenases (LOXs) are dioxygenases which catalyze the stereoselective addition of oxygen to arachidonic acid (AA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation is a common phenomenon present in the background of multiple neurodegenerative diseases, including AD. Previous studies showed that the key regulatory enzymes in the eicosanoid pathway, i.e., cyclooxygenase-2 and 5-, 12-, and 15-lipoxygenases, appear to have an important role in mediating the pro-inflammatory responses, providing further evidence that, in the future, it may be possible to manipulate pro-inflammatory pathways for therapeutic purposes [13]. Lipoxygenases (LOXs) are dioxygenases which catalyze the stereoselective addition of oxygen to arachidonic acid (AA).…”
Section: Introductionmentioning
confidence: 99%
“…[22] Wang et al [23] showed that 12-LOX activation plays a key role in oxidative injury due to glutathione (GSH) depletion. Inhibitors for 5-lipoxygenase (5-LOX) and cyclo-oxygenase 2 (COX-2 and 5-, 12-, and 15-LOX-inhibitor in astrocytes reduced significantly IL-6 secretion, compared to exposed glial cells without inhibitors [13]. Treatment with an inhibitor of all LOXs, namely nordihydroguaiaretic acid, or 5-LOX inhibitors, such as zileuton, BWB70C, and inhibitors of 12/15-LOX, baicalein and AA-861 (also an inhibitor of 5-LOX) significantly reduced, in a concentration-dependent manner, the level of lipid and protein oxidation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Literature reports that polyphenols shows antidiabetic activity by inhibition of carbohydrate hydrolyzing enzymes such as α-Amylase and α-Glucosidase 20,21 . Presence of polyphenols in the extract might have resulted in the inhibition of α-Amylase and α-Glucosidase.…”
Section: Fig 2a-f: Overlay Spectra Of Hplcmentioning
confidence: 99%
“…Inflammatory responses are regulated by oxidative enzymes belonging to the class of Lipoxygenase. These enzymes are related leukotrienes which are pro-inflammatory mediators 21 . F. esculentum has the capability of inhibiting 5-Lipoxygenase mRNA expression in IgE-sensitized RBL-2H3 cell 22 .…”
Section: Fig 2a-f: Overlay Spectra Of Hplcmentioning
confidence: 99%
“…Additional caution should be taken when dealing with the comparative neuropathology and neuropathogenesis of T. gondii infection, which could vary across different mammalian hosts. In this respect, while the cerebral inflammation's degree and severity in T. gondii meningoencephalitis-affected striped dolphins ( Stenella coeruleoalba ) (Di Guardo et al, 2010 ) has been shown to be positively correlated, on one side, with the brain tissue levels of 5-lipoxygenase (5-LOX) (Di Guardo et al, 2015 )—a key enzyme of the eicosanoid pathway mediating inflammatory reactions (Pihlaja et al, 2017 )—an excessive proinflammatory response has been reported, on the other side, in the brains of 5-LOX-deficient mice, which also succumbed to T. gondii infection at the early onset of chronic disease, following the development of severe encephalitic lesions (Aliberti et al, 2002 ).…”
mentioning
confidence: 99%